Mengukur Kesuksesan Penggunaan SIAKAD Menggunakan Model DeLone & McLean di Universitas Teknologi Sumbawa - Sumarningsih, Eka Yuni; Hudaya, Chairul; Hermanto, Koko (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The Sumbawa University of Technology uses an academic information system (SIAKAD) to improve the quality of academic administration services.  Based on the observations, there is a limited source of the information on the evaluation of SIAKAD at the University. Therefore, it is necessary to assess the SIAKAD performance as it can be used for further decision making and the development in leading the academic services. To achieve the research objectives, a success analysis was carried out using the DeLone and McLean success model and the Structural Equation Model (SEM) method with the Lisrel 8.8 program approach. The population in this study are 105 people which consisted of SIAKAD users at the Sumbawa University of Technology including lecturers, students, and staff.The results showed that the level of use of SIAKAD was 78%, the level of satisfaction with using SIAKAD was 91%, while the net benefit level of SIAKAD at the University of Technology Sumbawa was 54%.The Sumbawa University of Technology uses an academic information system (SIAKAD) to improve the quality of academic administration services.  Based on the observations, there is a limited source of the information on the evaluation of SIAKAD at the University. Therefore, it is necessary to assess the SIAKAD performance as it can be used for further decision making and the development in leading the academic services. To achieve the research objectives, a success analysis was carried out using the DeLone and McLean success model and the Structural Equation Model (SEM) method with the Lisrel 8.8 program approach. The population in this study are 105 people which consisted of SIAKAD users at the Sumbawa University of Technology including lecturers, students, and staff.The results showed that the level of use of SIAKAD was 78%, the level of satisfaction with using SIAKAD was 91%, while the net benefit level of SIAKAD at the University of Technology Sumbawa was 54%.